2017
DOI: 10.1002/pssb.201700271
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Properties of Reduced Graphene Oxide Buckypapers Obtained by Different Reduction Procedures

Abstract: Transmission properties of graphene oxide (GO) buckypapers reduced by different methods were investigated in the sub-THz range from 250 to 650 GHz. The reduction of GO films was performed by annealing and by interaction with hydrazine vapor. It was found that the chemical treatment is more effective for oxygen group removal than the thermal treatment. Based on the data of X-ray photoelectron and Raman spectroscopy measurements, the changes of the absorption properties of the investigated samples were attribute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The productive discussions during the meeting (which has been held on 19–24 March 2017) were provided by perfect organization and nice natural environment, including ski slopes, at Krasnaya Polyana resort (Sochi, Russia). The contributions (in total an amount of 30) of this Special Issue are covering research work related to production, characterization and application of the nanocarbon materials which include diamonds, carbon nanotubes, graphene other types of nanocarbon materials, and their composites . Traditionally for the NPO Workshop series there is also some portion of reports devoted to non‐carbon materials demonstrating properties and phenomena analogous to those observed for nanocarbons.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The productive discussions during the meeting (which has been held on 19–24 March 2017) were provided by perfect organization and nice natural environment, including ski slopes, at Krasnaya Polyana resort (Sochi, Russia). The contributions (in total an amount of 30) of this Special Issue are covering research work related to production, characterization and application of the nanocarbon materials which include diamonds, carbon nanotubes, graphene other types of nanocarbon materials, and their composites . Traditionally for the NPO Workshop series there is also some portion of reports devoted to non‐carbon materials demonstrating properties and phenomena analogous to those observed for nanocarbons.…”
mentioning
confidence: 99%
“…Most of the structural and other properties of carbon nanomaterials may be efficiently evaluated using traditional analytical techniques, such as XPS, Raman, electron microscopy, optical spectroscopy, etc. The papers presented in this Special Issue demonstrate also characterization of electrochemical, electromagnetic, and thermal properties of graphenic carbon structures. In the work of Kleshch et al it is shown that investigation of electron field emission may be used to reveal particular features of metallic and semiconducting carbon nanotubes .…”
mentioning
confidence: 99%